Glacier zonation and velocity estimations on Axel Heiberg Island using TerraSAR-X data - Hauser, Sahra; Wendleder, Anna; Roth, Achim; van Wychen, Wesley; Thomson, Laura (2021)
The cryosphere and particularly glaciers and ice sheets play a fundamental role in the global climate system and are strongly influenced by changes in the system itself. The cryosphere refers to frozen components of the Earth system that are at or below the land and ocean surface. These include snow, glaciers, ice sheets, ice shelves, icebergs, sea ice, lake ice, river ice, permafrost, and seasonally frozen ground. As integral parts of the Earth system, the Polar Regions interact with the rest of the world through shared ocean, atmosphere, ecological, and social systems; notably, they are key components of the global climate system. The spatial footprints of the Polar Regions include a vast share of the world’s ocean and cryosphere: they encompass surface areas equalling 20% of the global ocean and more than 90% of the world’s continuous and discontinuous permafrost area, 69% of the world’s glacier area including both of the world’s ice sheets, almost all of the world’s sea ice, and land areas with the most persistent winter snow cover (Meredith et al. 2019). Over the past two decades, Arctic surface temperature has increased by more than twice the global average (Notz and Stroeve 2016; Richter-Menge et al. 2017). Attribution studies show the significant role of anthropogenic increases in greenhouse gases in the observable increase in Arctic surface temperature (Fyfe et al. 2013; Najafi et al. 2015), so there is high confidence in projections of further Arctic warming (Overland et al. 2019). The mechanisms for Arctic amplification are still under debate, but they include decreased albedo in summer due to loss of sea ice and snow cover, increase in total water vapour content in the Arctic atmosphere, changes in total cloud cover in summer, additional heat generated by newly formed sea ice over more extensive open water areas in the fall, transport of heat and moisture northward, and lower rate of heat loss to space from the Arctic (Pithan and Mauritsen 2014). The Canadian Arctic Archipelago (CAA), located off the ...